2018
DOI: 10.1103/physrevd.98.023536
|View full text |Cite
|
Sign up to set email alerts
|

Merger rate of a subdominant population of primordial black holes

Abstract: The formation of astrophysical and primordial black holes influences the distribution of dark matter surrounding them. Black holes are thus expected to carry a dark matter 'dress' whose properties depend on their formation mechanism and on the properties of the environment. Here we carry out a numerical and analytical study of the merger of dressed black holes, and show that the distribution of dark matter around them dramatically affects the dynamical evolution of the binaries. Although the final impact on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
144
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(152 citation statements)
references
References 73 publications
7
144
1
Order By: Relevance
“…Ref. [91] studied the interaction of pairs of PBH initially clothed by PDM. They find that as the PBH orbit, they lose their PDM halos and dynamical friction effects tend to circularize and shrink the orbit.…”
Section: Resultsmentioning
confidence: 99%
“…Ref. [91] studied the interaction of pairs of PBH initially clothed by PDM. They find that as the PBH orbit, they lose their PDM halos and dynamical friction effects tend to circularize and shrink the orbit.…”
Section: Resultsmentioning
confidence: 99%
“…The progenitors of these BBHs are still unknown and under intensively investigation (see e.g. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]). These LIGO/Virgo BBHs present a much heavier mass distribution (in particular the sourceframe primary mass of GW170729 event can be as heavy as 50.2 +16.2 −10.2 M [7]) than that inferred from X-ray observations [28][29][30][31], which would challenge the formation and evolution mechanisms of astrophysical black holes.…”
Section: Introductionmentioning
confidence: 99%
“…Black holes (BHs) produced prior to big bang nucleosynthesis (BBN), i.e., primordial black holes (PBHs), represent such an alternative -remarkably, this solution is as old as particle dark matter [5]. In particular, this scenario has recently attracted much attention [6][7][8][9][10][11][12] in the context of the LIGO and VIRGO discoveries of several binary BH mergers [13][14][15][16][17].The idea that PBHs could be formed by strong accretion during the radiation-dominated epoch was first introduced five decades ago [18]. It was later suggested that initial fluctuations in the early Universe could give rise to a large number of gravitationally collapsed objects with masses above the Planck mass [19], that however, would not grow substantially by accretion [20].…”
mentioning
confidence: 99%